The museum as muse artists reflect - McShine, Kynaston (New York : Harry N. Abrams, 1999)
Acconci, Vito ; Arnold, Eve ; Art & Language ; Asher, Michael ; Baumgarten, Lothar ; Bloom, Barbara ; Boltanski, Christian ; Broodthaers, Marcel ; Buren, Daniel ; Calle, Sophie ; Cardiff, Janet ; Cartier-Bresson, Henri ; Christo ; Cornell, Joseph ; Dibbets, Jan ; Dille, Lutz ; Dion, Mark ; Distel, Herbert ; Duchamp, Marcel ; Ericson, Kate ; Erwitt, Elliott ; Fenton, Roger ; Filliou, Robert ; Fink, Larry ; Fluxus ; etc.
+ bijlage: Catalog Deaccessions 1929 through 1998 by Michael Asher
exhibition: The Museum as Muse: Artists Reflect, organized by Kynaston McShine, Museum of Modern Art, New York, March 14 - June 1, 1999
boek